Supporting data collection in wireless sensor networks : from energy conserving to perpetual living - Xiang, Liu (2013)
Wireless sensor networks (WSNs) with their networked sensor nodes, though powerful in monitoring the physical environment by integrating the information in large scale, are deficient in energy aspect due to the resource constrained design. Aiming at energy conservation in WSNs or lifetime elongation, energy-aware protocols have been inten- sively studied by the community. Among those proposals, data collection, arguably the most fundamental function of a WSN, attracts most of the research efforts. Whereas most approaches bargain for every piece of energy in this scenario, another trend of research seeks for recharging the networked nodes via external power resources. In this thesis, we first follow the traditional way by developing an energy efficient data collection scheme, then we take a step further by supporting the network through wire- less power transfer. In this way, we strive to make WSNs from energy conserving to perpetual living.